Determination of Heavy Metals in Soils Around Afsin-Elbistan Thermal Power Plant (Kahramanmaras, Turkey) - Tumuklu, Ali; Ciflikli, Murat; Zafer Ozgur, F. (Asian Journal of Chemistry, 2010)
In this study, heavy metal (V, Ti, Cr, Mn, Ni, Cu, Zn, As, Sn, Al, Mg and Fe) pollution of the soils around Afsin-Elbistan Thermal Power Plant have been investigated. When the average values of the 21 analysis results were compared with the crystal values, V:1.03, Ti:0.64, Cr:3.51, Mn:1.02, Ni:6.48, Cu:3.31, Zn:1.56, As:3.09, Sn:0.51, Al:0.71, Mg:1.25 and Fe:1.25 values were determined. According to these comparisons, the exchange rates in the study area are as follows: Ni > Cr > Cu > As > Mg and Fe > Zn. According to the relationships between distance and sampling locations of the samples (sample numbers 1-16) collected through a line from the area between power plant and Afsin district, distances (km) where the elements were determined in their maximum values are as follows: Ni:3, Mg:3, Cr:5, Ti:8, Mn:8, Cu:8, Fe:9, V:9, Zn:9, As:9, Sn:14 and Al:15. According to the results of XRD whole rock analysis, mineral associations found as clay, calcite, quartz, feldspar, mica, hematite and rarely clinoptilolite and opal-CT. Clay mineral assemblages are montmorillonite, illite, kaolinite, notronite and halloysite.